Preparation of SDF-1α-loaded electrospun coaxial microspheres and their study on promoting migration and differentiation of dental pulp stem cells - Wenjie Feng; Chao Li; Qun An; Shaojing Shi; Yuanfei Wang; Guanfan Lu; Degang Sun (Frontiers in Materials, 2025)
IntroductionRoot canal therapy (RCT) is the most common treatment for pulpitis or pulp necrosis. However, in immature permanent teeth, loss of pulp vitality hampers root development and apical closure, resulting in thin and fragile dentin walls. Regenerative endodontic treatment (RET) has emerged as a promising approach to restore pulp vitality and promote root maturation. Stromal cell-derived factor-1α (SDF-1α), a key chemokine, has shown significant potential in enhancing the migration and odontogenic differentiation of human dental pulp stem cells (hDPSCs).MethodsTo protect the bioactivity of SDF-1α during delivery and achieve controlled release, we fabricated core-shell structured SDF-1α/poly(lactic-co-glycolic acid) (PLGA) microspheres using electrospinning technology. The morphology, release profile, and biocompatibility of the microspheres were characterized, and their effects on hDPSC migration and differentiation were evaluated in vitro.ResultsThe core-shell microspheres demonstrated uniform particle size, excellent biocompatibility, and sustained-release behavior. SDF-1α released during the first two weeks significantly promoted the migration of hDPSCs, confirming the preservation of its bioactivity. Furthermore, the microspheres continuously induced the odontogenic and angiogenic differentiation of hDPSCs without requiring repeated administration.DiscussionThese findings suggest that the sustained-release SDF-1α/PLGA microspheres effectively maintain growth factor activity, support long-term therapeutic outcomes, and enhance the efficiency of RET. Their ability to promote hDPSC migration and differentiation positions them as a promising scaffold component for future pulp regeneration applications.